Assessing the impact of rice cultivation and off-season period on dynamics of soil enzyme activities and bacterial communities in two agro-ecological regions of Mozambique - Ezeokoli, Obinna T.; Nuaila, Valter N. A.; Obieze, Chinedu C.; Muetanene, Belo A.; Fraga, Irene; Tesinde, Maria Natalia; Ndayiragije, Alexis; Coutinho, João; Melo, Ana M. P.; Adeleke, Rasheed A.; Ribeiro-Barros, Ana I.; Fangueiro, David (MDPI, 2021)
Soil ecosystem perturbation due to agronomic practices can negatively impact soil productivity by altering the diversity and function of soil health determinants. Currently, the influence of rice cultivation and off-season periods on the dynamics of soil health determinants is unclear. Therefore, soil enzyme activities (EAs) and bacterial community compositions in rice-cultivated fields at postharvest (PH) and after a 5-month off-season period (5mR), and fallow-fields (5-years-fallow, 5YF; 10-years-fallow, 10YF and/or one-year-fallow, 1YF) were assessed in two agroecological regions of Mozambique. EAs were mostly higher in fallow fields than in PH, with significant (p < 0.05) differences detected for β-glucosidase and acid phosphatase activities. Only β-glucosidase activity was significantly (p < 0.05) different between PH and 5mR, suggesting that β-glucosidase is responsive in the short-term. Bacterial diversity was highest in rice-cultivated soil and correlated with NO3−, NH4+ and electrical conductivity. Differentially abundant genera, such as Agromyces, Bacillus, Desulfuromonas, Gaiella, Lysobacter, Micromonospora, Norcadiodes, Rubrobacter, Solirubrobacter and Sphingomonas were mostly associated with fallow and 5mR fields, suggesting either negative effects of rice cultivation or the fallow period aided their recovery. Overall, rice cultivation and chemical parameters influenced certain EAs and shaped bacterial communities. Furthermore, the 5-month off-season period facilitates nutrient recovery and proliferation of plant-growth-promoting bacteria.